Influence of hypnotic suggestions to increase periodontal patients' compliance / Abdul Halim R ... [et al.] - Rohaida, Abdul Halim; H A, Mohamad; A S, Zulkiflee; E, Noor (Faculty of Dentistry, Universiti Teknologi MARA, 2021)
Objective: To evaluate the effectiveness of hypnosis 1) to reduce dental anxiety in periodontal patients, and 2) to increase periodontal patients' compliance through the reduction of dental anxiety. Methods: This was a randomized control trial of 22 patients (13 males, 9 females; 40.14 ± 19.59 years) who underwent non-surgical periodontal therapy in the Postgraduate and Undergraduate Clinics. Patients were divided into the case, H, (hypnosis; n=11) and controlled, N, (no hypnosis; n=11) groups, where patients' dental anxiety level was assessed twice for both groups using IDAF-4C+ during the first visit and the second visit. The compliance was evaluated during the follow-up visit. Results: The result showed statistically significant differences (p < 0.05) in the H group during the second visit indicating a reduction in dental anxiety as compared to N group. However, there were no statistically significant differences (p > 0.05) in the pattern of reduction of blood pressure between both case and control groups. Based on the heart rate, patients were found to be more relaxed with hypnotherapy at the beginning of the treatment but halfway through, patients without hypnotherapy had a more significant reduction in heart rate level. Conclusion: Hypnotic suggestions were found to help reduce patient's fear and anxiety. However, the compliance of the patients with or without hypnotherapy proved to have a similar outcome.